AB0122 In Vivo Intraarticular Binding of A Biopolymeric Compound in the Course of Experimental Immune Complex Induced Arthritis, Evaluated as A Potential Tool for Targeting Inflamed Synovium. (10th June 2014) - Fischetti, F.; Durigutto, P.; Biffi, S.; De Nardo, D.; Paoletti, S.; Marzari, R.; Sblattero, D.; Macor, P.
Abstract : Objectives: To evaluate in an in vivo rat experimental model of antigen induced arthritis (AIA) the concentration and persistence of intraarticular (ia) binding of a biocompatible modified polysaccharide, composed of a chitosan backbone compound (Chitlac) (CTL), when administered soon after the induction of arthritis, and analyze any interaction with inflammatory synovial tissue development, in order to assess its possible use as a tool for drug targeting of inflamed synovium. Synovial tissue delivery and the effects on molecular and structural arthritic modifications were compared with those induced by a previously described modified joint tissue-specific anti-C5 recombinant antibody MT07 provided with a homing peptide (Adienne Pharma & Biotech) Methods: In 3 groups, each consisting of 4 male wistar rats, monoarthritis (knee joint) was induced by ia injection of 100 μg of methylated bovine serum albumin (mBSA), following previous immunization to mBSA+Freund's adjuvant. Arthritis development was monitored at least for a 10 days long period by joint swelling (JS) measurements and, further, ex vivo analyses of synovial washing cell counts, TNF-α and IL-6 concentrations, and histomorphology were performed. Soon after (24 hrs) arthritis induction, the 3 groups of rats were iv injected with the fluorophore Cy5.5 (FluoroLink, Amersham Biosciences) 0.05mg/ml alone (CNT), or by the CTL-Cy5.5, or MT07-Cy5.5 bound molecules, respectively, diluted in a 0.1 M sodium carbonate buffer solution. A small-animal time-domain Optix MX preclinical near-infrared imager (Advanced Research Technologies, NL) was used for the in vivo evaluation of Cy5.5-labeled molecules. Two-dimensional scanning regions of interest were selected. The data were recorded as point-spread functions, and the images were reconstructed as fluorescence intensity. Anesthetized rats were checked for imaging of fluorophore distribution at several times before being euthanized for ex vivo joint tissue evaluations, and detection of the tested molecules in other organs Results: In both the CNT and CTL treated groups, joint swelling increased to a 25-30% degree from basal levels (p<0.001) and comparable degrees of swelling were observed up to 10 days. Treatment with MT07 produced instead a 70% stable decrease of JS (p<0.001). Differently to MT07, which significantly reduced TNF-α and IL-6 contents, as well as neutrophyls counts (p<0.01), and histomorphology damage score (p<0.05), CTL infusion was not able to modify any of the ex vivo evaluated, arthritis-related parameters. While being different the mean degree of joint fluorescence intensity (either inflamed or not) recorded in CTL, or MT07 treated animals (3.45x10 3 vs 6.7x10 3 in the arthritic joint, at time=10 days; p<0.001), CTL binding showed a stable and increasing, time related, degree of concentration, thus proving evidence of its possible usefulness in targeting therapeutic or diagnostic drugs in conditions of immune-mediated arthritis Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3652